Etudes géologiques et géotechniques d’un pont sur oued Boudouaou. Wilaya de Boumerdès - Hattab ,Imad Eddine; Dr. Merdas.A(Encadreur) (Université Ferhat Abbas Sétif 1. institut d'architecture et sciences de la terre. département de géologie, 2017)
The main objective of our thesis is to be able to use the various geological, geotechnical and hydroclimatological tools as well as the tests carried out to calculate the foundations of a structure. The primary studies that precede the construction of the bridge planned at BOUDOUAOU, aim to put in place rules that allow us to construct any structure of art according to the recommended norms. The operation and processing of the data ensures that there will be no damage that could affect our structure
الهدف الاساس لمذكرتنا هو التمكن من استعمال مختلف ادوات الدراسات الج وٌلوج ةٌ، الج وٌتقن ةٌ و اله دٌرومناخ ةٌ بالإضافة للتجارب المنجزة من أجل حساب الأساسات لمشروع فن .ً الدراسات للأول ةٌ الت تسبق إنجاز الجسر المتوقع إنجازه ببودواو، تهدف إلى وضع قواعد تمكننا من بناء أي منشأة فن ةٌ و ذلك بإحترام المعا رٌٌ المطلوبة. إستغلال و معالجةالمعط اٌت تضمن عدم حدوث كوارث الت مٌكنها أن تمس منشأتنا الفن ةٌ.
Keywords: Essais; Pont; Géologie; Géotechnique; Hydroclimatologie